Impacts of reindeer on soil carbon storage in the seasonally frozen ground of northern Finland:A pilot study - Windirsch, Torben; Forbes, Bruce C.; Grosse, Guido; Wolter, Juliane; Stark, Sari; Treat, Claire; Ulrich, Mathias; Fuchs, Matthias; Olofsson, Johan; Kumpula, Timo; Macias-Fauria, Marc; Strauss, Jens (2023)
To test the effect of reindeer husbandry on soil carbon storage of seasonally frozen ground, we analysed soil and vegetation properties in peatlands and mixed pine and mountain birch forests. We analysed sites with no grazing and contrasting intensities of grazing, and associated trampling, in Northern Finland. With a pilot study approach, we optimised the study design to include several grazing class sites including grazing seasonality but omitting sample replication at one site. Soils were analysed for water content, bulk density, total organic carbon (TOC), total nitrogen, stable carbon isotopes and radiocarbon ages. We found that there was no significant difference between grazing intensities in terms of TOC, but that TOC mainly depended on the soils' TOC content present prior to intensive herbivory introduction. In contrast, understory vegetation was visibly transformed from dwarf shrub to graminoid-dominated vegetation with increasing grazing and trampling intensity. Also, we found a decrease in bulk density with increasing animal activity on soil sites, which most likely results from named vegetation changes and therefore different peat structures.